Sexual Maturation in the Female Göttingen Minipig. (April 2016) - Peter, Birgit; De Rijk, Eveline P. C. T.; Zeltner, Adrian; Emmen, Henricus H.
In the literature, experimental data on sexual maturation of female Göttingen minipigs are lacking. This may impede a reliable evaluation of reproductive functioning, particularly in the young (immature) sow used in toxicity studies. To find suitable method(s) to detect ovulation during in-life, a pilot study was performed with 3 adult sows (approximately 10–11 months), followed by a study with 14 immature females (approximately 3–4 months). From the tested parameters, progesterone analysis was the most reliable predictor. First progesterone peaks were observed in 13 sows at 3.7–4.2 or 5.5–6.5 months with a cycle length of 17–22 days. One sow did not show progesterone release until necropsy at 7 months of age. Histopathology of the reproductive organs confirmed sexual maturity for all sows, except the one without progesterone peak. In conclusion, the age range of sexual maturity of female Göttingen minipigs (3.7–6.5 months) is much wider than previously thought, and in-life progesterone analysis is a useful tool to determine sexual maturity of individual animals.